AN EXPLORATION OF SOCIAL ROLES, ROLE CONFLICT, AND OLDER ADULT VOLUNTEER PARTICIPATION AND SATISFACTION. (16th November 2018) - Crittenden, J; Butler, S
Abstract: This research examines the extent to which role conflict is experienced by older adult volunteers and explores the relationship between role conflict, role load (# of roles held by an older adult), and volunteer satisfaction, intent to remain in the volunteer role, and participation in formal volunteering. Role conflict is defined as conflict that arises when the demands of one's social roles outstrip the personal resources available to meet those demands (Goode, 1960). A survey was conducted with national sample of older adult volunteers, ages 55–97, drawn from 55 Retired and Senior Volunteer Programs. Volunteers (N= 1, 697), reported an average of 22.6 hours (SD = 24.04) per month of formal volunteering and an average of 1.19 roles (SD = .796) in addition to formal volunteer work. The most frequent role reported was informal volunteer (78.7%), followed by caregiver (35%) and paid worker (14.1%). Role load, or aggregate role count, was weakly, but significantly, correlated with self-reported experience of role-related conflict for caregiving (r =.463), informal volunteering (r =.395), and paid employment (r =.390). Role conflict was weakly but significantly correlated with volunteer satisfaction (r = -.092) and intent to remain in the volunteer role (r = -.088). Role conflict was not significantly correlated with formal volunteer participation and role load demonstrated a weak, but significant, correlation with participation (r = -.065). The sample demonstrated low levels of conflict overall suggesting that formal volunteers may utilize personal strategies for mitigating role conflict. Follow-up research will further explore volunteer role enhancement strategies.